Membangun Merek Melalui Penyelenggaraan Sebuah Event: Studi Kasus Pada Event “Sour Sally Just Wanna Have Fun” - Prida Ariani Ambar Astuti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2011)
A brand enables customers to remember the core information about a product, and prevent competitors from making imitations (Aaker, 1991 ). Successful brand building helps profitability by adding value that entices customers to buy (De Chernatorny and McDonald, 1994). It is also becoming clearer that companies creating strong brands can obtain important competitive advantage over those that do not (Kohli and Thakor, 1997). Event more firms and other organizations have come to the realization that one of their most valuable assets is the brand names associated with their products or services. Brands themselves may be linked to other entities that have their own knowledge structures in the minds of consumers. A brand may seem more likable or perhaps event trustworthy or expert by virtue of becoming linked to an event. The result showed that the event “Sour Sally Just Wanna Have Fun” can strongly affect the brand of the members that joined in the Facebook group. Through the stages in brand building blocks namely at the stage of salience 70.69%, performance 74,04%, judgments 73.72%, feelings 69.79%, and resonance 64.44%.